Attitudes toward Caring for Older Parents: The Role of Cultural and Sociodemographic Variables - Nagihan Taşdemir (Psikoloji Çalışmaları)
This paper presents research that investigated attitudes toward caring for older parents, including filial obligation norms and the intention to support parents in the future. It explores the relationship between these attitudes and cultural values (relatedness and autonomy and instrumental and psychological values of chilldren) and sociodemographic factors (family living situation, maternal and paternal educational levels). This study involved 364 university students who completed the measures of filial obligation norms, intention to support parents in the future, cultural values, value of children, and sociodemographic variables. Results indicated that participants from urban areas were less inclined to endorse material family obligation norms and instrumental and psychological values of children compared with their non-urban counterparts, reflecting lower levels of collectivist tendencies. Moreover, participants with lower maternal educational levels demonstrated higher levels of children’s instrumental value, highlighting their emphasis on intergenerational dependencies. Similarly, those with lower paternal educational levels demonstrated higher endorsement of material and emotional filial obligation norms, as well as instrumental and psychological values of children, indicating stronger collectivist tendencies. Hierarchal regression analyses revealed that paternal education level, instrumental and psychological values of children, and relatedness values predicted material filial obligation norms, while psychological values of children and relatedness values predicted emotional filial obligation norms. Furthermore, the intention to support parents in the future was predicted by gender and material filial obligation norms. In the context of relevant literature, the results show a decline in familial and intergenerational collectivist characteristics, as well as instrumental and psychological values of children, in Türkiye with socioeconomic development. The intention to support parents in the future was associated with hierarchy-oriented filial obligation norms. These findings are significant for informing family change models and the development of social policies aimed at caring for older people.